Bioactivity studies on the leaves of Talisai, Terminalia catappa (Linn.) family combretaceae, Alugbati Basella rubra (Linn.) family basellaceaf and hagonoi wedelia biflora (Linn.) family compositae. - Castillo, Mae Ann Hofilena (1999.)
The aqueous extracts from the of hagonoi, Wedelia biflora (linn.)Family Compositae, talisai Terminalia catappa (Linn.) Family Combretaceae and alugbati Basella rubra (Linn.) Family Basellaceae were bioassayed for analgesic, antipasmodic antimicrobial and toxic activities using acetic acid writhing assay, charcoal tracing assay, the paper disc diffusion technique and the brine shrimp lethality bioassay respectively. Talisai, Terminalia catappa (Linn.) was found to be the most bioactive having toxic, antimicrobial and a little of analgesic activity. , Sequential extraction of the most bioactive plant yielded and the n-hexane, dichloromethane, ethyl acetate and aqueous extracts. Bioassay result showed tha aqueous extract as the most active against brine shrimps. The fractions contain tannins, flavonoids, anthraquinone and simple phenolics as determined by chemical means.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Talisai, Leaves; Terminalia catappa